An overview of research on the association between microplastics and central nervous system disorders - Shi, Xiaohua; Wang, Yukai; Xu, Lei (Frontiers in Public Health, 2025)
As plastic pollution continues to escalate, microplastics have emerged as a major global contaminant, raising significant concerns about their potential effects on human health. In recent years, the widespread presence of microplastics has been linked to various health problems, particularly their impact on central nervous system (CNS) disorders, which are increasingly becoming a focus of scientific research. Current evidence indicates that microplastics can enter the human body through inhalation, ingestion, and skin absorption. Once they penetrate the body, these particles can accumulate in neural tissues, leading to detrimental changes such as inflammation, oxidative stress, and neuronal damage. This review aims to systematically explore the correlation between microplastic exposure and central nervous system disorders, analyze and summarize the underlying mechanisms, and provide a scientific basis for public health risk assessment and environmental policy formulation.